The effect of personal selling on the sales of alcoholic beverages Ghana, the mediating role of customer service. - Agarigo, Williams Anamziriya (KNUST, 2025)
A Thesis Submitted In Partial Fulfillment Of The Requirements For The Degree Of Master Of Business Administration (Marketing Option).